Perbedaan Tingkat Kecemasan Ibu Primigravida Dan Multigravida Dalam Menghadapi Persalinandi Bps Ny. Ensriah Â Amd.Keb - Sudarsih, Sri; Amalia Rahmawati, Nova (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractExpectant mothers who usually complain when they pregnant are those in the third trimester, as for the reason arc because they worry about childbirth. The difference of anxiety level between primigravida and multigravida is primarily on the experience a5pect. This research aims to compare the difference of anxiety level of the respondents at BPS Ky. Ensriah Amd.Keb and it is analytical research using cross sectional design. The populations are 28 primigravida and multigravida mothers which on their third trimester. The sampling technique is using nonprobabiliry sampling with purposive sampling type. There are 20 samples which convenience with inclusion and exclusion criteria. Variable used in this research arc the anxiety level ofprimagravida and multigravida. The data arc obtained through HARS questionnaire.The results are tested using I-test with SPSS V.16 software. The results show that P < rt with 0,000 < 0,05 and t value.400 > 1 tabel 2.086. That means H0 is rejected and H1 is accepted so there is an anxiety level difference experienced byprimigravida and multigravida when facing childbirth at BPS Ny. Ensriah Amd.Kcb. Primagravida experiences moderate level of anxiety while multigravida experience low level of it and it is caused by their experience of giving birth. In addition, their profession and education level also play significant role on their anxiety level. Provision of health education is important to supperss excessive anxiety level for expectant mothers in the face of pregnancy and childbirth.Keywords: anxiety level, primigravida, multigravida